Diseño de un sistema de costos por procesos para la industria de alimentos extra (indalex), ubicado en el cantón Saquisili provincia de Cotopaxi, en el período del 01 de noviembre al 31 de diciembre del 2013 - Ilaquiche Vega, Nelly Margoth (2015)
It has been developed according to several theoretical contents that has been the main base for the development this research, it was carried out in the Industry of extra food (INDALEX) through a quick analysis on the internal environment company, in order to know the movements made in the Administration and Production for determining the Costs and productive expenditures incurred in the production departments. Different researching methods applied to the organization’s members helped to know different needs and problems existing in the Industry, by applying them the respective proposal may be corrected in benefit of all who make up the Noodle Factory (INDALEX)....